2020
DOI: 10.4236/ape.2020.103020
|View full text |Cite
|
Sign up to set email alerts
|

Active Breaks and Motor Competencies Development in Primary School: A Systematic Review

Abstract: The integration of physical activity into the school day is a key aspect for the promotion of "comprehensive school physical activity programs". The proposal of physical activity breaks, known as "Active Breaks" may provide an opportunity to extend the practice of motor activity during curricular hours, alternating too many sedentary moments with short-term physical activity. The aim was to determine the effectiveness of Active Breaks use on motor performance, cognitive engagement and psychological correlates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In addition to the abovementioned benefits of school-based physical activity interventions, other studies have reported positive effects on children's self-reported psychological well-being, social and peer support, and the school environment [45]. Thus school could be an ideal setting for increasing physical activity levels, as it is the place where children spend most of their day during childhood [46]. Thus, this provides an opportunity for teachers (both generalist and PE teachers) to help anchor experiences in a didactic pedagogical and curricular framework in which pupils' learning and health promotion processes are developed [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the abovementioned benefits of school-based physical activity interventions, other studies have reported positive effects on children's self-reported psychological well-being, social and peer support, and the school environment [45]. Thus school could be an ideal setting for increasing physical activity levels, as it is the place where children spend most of their day during childhood [46]. Thus, this provides an opportunity for teachers (both generalist and PE teachers) to help anchor experiences in a didactic pedagogical and curricular framework in which pupils' learning and health promotion processes are developed [46].…”
Section: Discussionmentioning
confidence: 99%
“…Thus school could be an ideal setting for increasing physical activity levels, as it is the place where children spend most of their day during childhood [46]. Thus, this provides an opportunity for teachers (both generalist and PE teachers) to help anchor experiences in a didactic pedagogical and curricular framework in which pupils' learning and health promotion processes are developed [46].…”
Section: Discussionmentioning
confidence: 99%
“…The integration of physical activity into the school routine is a key aspect to reduce sedentary behaviors. Elementary schools can be ideal settings for physical activity in children due to the amount of time spent at school and, in addition, due to the safe place with education professionals, who can direct not only the physical activity practice, but also include educational content ( 11 ). However, assigning more time for physical activity during the daily school often conflicts with the curricular demands, hiding physical activities promotion policies.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews ( 11 , 15 , 18 ) proposed three approaches to implementing active breaks: (1) Active breaks as an interval/rest between two successive lessons; (2) Active breaks taken during the lesson; (3) Physical activity classes, with physical activity integrated into other subjects (e.g., mathematics, history, etc.). These multiple alternatives has shown to be limited due to a very broad school curriculum and the established priority for standardized tests ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…The physiological and technical demands analysis of élite sport Sgrò & Lipoma, 2016) does not allow, during the training phase, to limit oneself to the conditional aspects or to counteract the involution of motor skills due to sedentary lifestyles (Greier et al, 2020;Colella et al, 2020;D'Elia, 2020;Esposito et al, 2020).…”
Section: Introductionmentioning
confidence: 99%